Molecular Imaging of Tumor Microenvironment to Assess the Effects of Locoregional Treatment for Hepatocellular Carcinoma. Issue 4 (5th November 2021) - Chen, Quan; Chen, Austin Z.; Jia, Guorong; Li, Jindian; Zheng, Chuansheng; Chen, Kai
Abstract : Liver cancer is one of the leading causes of cancer deaths worldwide. Among all primary liver cancers, hepatocellular carcinoma (HCC) is the most common type, representing 75%‐85% of all primary liver cancer cases. Median survival following diagnosis of HCC is approximately 6 to 20 months due to late diagnosis in its course and few effective treatment options. Interventional therapy with minimal invasiveness is recognized as a promising treatment for HCC. However, due to the heterogeneity of HCC and the complexity of the tumor microenvironment, the long‐term efficacy of treatment for HCC remains a challenge in the clinic. Tumor microenvironment, including factors such as hypoxia, angiogenesis, low extracellular pH, interstitial fluid pressure, aerobic glycolysis, and various immune responses, has emerged as a key contributor to tumor residual and progression after locoregional treatment for HCC. New approaches to noninvasively assess the treatment response and assist in the clinical decision‐making process are therefore urgently needed. Molecular imaging tools enabling such an assessment may significantly advance clinical practice by allowing real‐time optimization of treatment protocols for the individual patient. This review discusses recent advances in the application of molecular imaging technologies for noninvasively assessing changes occurring in the microenvironment of HCC after locoregional treatment.